Optimalisasi Pelaksanaan Pidana Mati Dalam Mewujudkan Efek Jera Pada Tindak Pidana Pembunuhan Berencana - Rahadjo Puro, Djuhandhani; Sudarmanto, Kukuh; Arifin, Zaenal (JURNAL USM LAW REVIEW, 2023)
The purpose of this research is to examine the implementation of the death penalty and the commutation of death sentences for premeditated murder cases. The urgency of this research lies in how the application of the death penalty in proven premeditated murder cases may fail to ensure legal justice for the victims. This type of research adopts a socio-legal research approach. The legal framework for the application of the death penalty in Indonesia is governed by Article 10 and Article 11 of the Criminal Code (KUH Pidana). In the case of premeditated murder of S and her child MF, the defendant D was ultimately sentenced to life imprisonment. Defendant D was charged under Article 340 of the KUHP (Criminal Code), Article 80 in conjunction with 76c of Law Number 35 of 2014 concerning child protection in Indonesia. The imposition of the death penalty for premeditated murder cases is rarely decided by judges. In their judgments, judges often opt for life imprisonment or a 20-year prison sentence. Tujuan penelitian ini untuk mengkaji pengaturan pelaksanaan hukuman mati dan pemutusan hukuman mati terhadap pembunuhan berencana. Urgensi penelitian ini adalah bagaimana penerapan hukuman mati pada kasus pembunuhan berencana terbukti kurang mampu menjamin keadilan hukum bagi korban. Jenis penelitian ini menggunakan jenis penelitian yuridis sosiologis. Kerangka hukum penerapan hukuman mati di Indonesia diatur dalam Pasal 10 dan Pasal 11 KUH Pidana. Untuk kasus pembunuhan berencana terhadap S dan anaknya MF pada akhirnya terdakwa D dijatuhi hukumam pidana seumur hidup. Terdakwa D dikenai Pasal 340 KUHP, Pasal 80 juncto 76c UU RI Nomor 35 Tahun 2014 tentang perlindungan anak. Penerapan hukuman mati pada tindak pidana pembunuhan berencana jarang diputuskan oleh hakim. Dalam putusannya Hakim menggunakan pidana seumur hidup atau hukuman penjara 20 tahun.